2014
DOI: 10.1109/tvcg.2014.2346983
|View full text |Cite
|
Sign up to set email alerts
|

The relation between visualization size, grouping, and user performance

Abstract: In this paper we make the following contributions: (1) we describe how the grouping, quantity, and size of visual marks affects search time based on the results from two experiments; (2) we report how search performance relates to self-reported difficulty in finding the target for different display types; and (3) we present design guidelines based on our findings to facilitate the design of effective visualizations. Both Experiment 1 and 2 asked participants to search for a unique target in colored visualizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…For instance, different bar chart designs impact accuracy [8], the ratio of line-charts and use of dual-line charts effect the choices people make under uncertainty [1] and visual perception can constrain the use of colour in visualisations [9], particularly in maps [10]. In addition, the grouping, quantity, and size of visual marks has been shown to affect 'visual search' perceptual efficiency [11].…”
Section: Design Spacesmentioning
confidence: 99%
“…For instance, different bar chart designs impact accuracy [8], the ratio of line-charts and use of dual-line charts effect the choices people make under uncertainty [1] and visual perception can constrain the use of colour in visualisations [9], particularly in maps [10]. In addition, the grouping, quantity, and size of visual marks has been shown to affect 'visual search' perceptual efficiency [11].…”
Section: Design Spacesmentioning
confidence: 99%
“…Volume, variety, and velocity are attributes of 'big data' [8,22] that make it impossible for a (human) dataproduct designer to account for all possible future visual representations. For example, increasing the dots shown in a scatter plot reduces the accuracy of visual search tasks [13]. With this in mind, the effectiveness of a scatterplot may change over time given changes in the volume of data.…”
Section: Data Representationmentioning
confidence: 99%
“…Do data visualization design elements, such as color, size, and data grouping affect user performance? To test such a premise, an experiment was conducted whereby participants were asked to find a target within a visual (Gramazio, Schloss, & Laidlaw, 2014). Two experiments were conducted, one using a scatterplot and one depicting squares within a grid.…”
Section: Literature Analysismentioning
confidence: 99%
“…The results of the scatterplot and grid experiments concluded that color layout, quantity, and size of the marks impact on visual search time, impacting user performance (Gramazio et al, 2014;Ware, 2012).…”
Section: Literature Analysismentioning
confidence: 99%
See 1 more Smart Citation